Aplikasi Passing Grade Program Studi Perguruan Tinggi Negeri di Indonesia dengan Menerapkan Algoritma Zhu Takaoka - Sahri, Ahmadin (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Passing Grades are often used as a benchmark for opportunities or considerations of graduation to college. And from the passing grade, we can also see the level of graduation to the state higher education study program, because if the passing grade is higher then the graduation level of the study program is lower and vice versa, if the passing grade is getting lower then the higher the level of graduation to the study program . The problem that occurs is the knowledge of the passing grade, because every student does not know about the passing grade of each major at a state tertiary institution in Indonesia. Which will make students / i will be hesitant and hesitant to choose majors and colleges that have the opportunity and ability of students to achieve majors and colleges that students want. Based on the above problems will be solved using the string maching algorithm, the zhu takaoka algorithm. Which will do the character or criteria matching and will bring up output that has the same or matching. In addition this research is based on Android, which will enable its use to be faster, easier and efficient.